Clinical effectiveness of hemoglobin spray (Granulox®) as adjunctive therapy in the treatment of chronic diabetic foot ulcers. Issue 1 (1st January 2016) - Hunt, Sharon D.; Elg, Fredrik
Abstract : Introduction: Hemoglobin spray (Granulox ® ) comprises purified hemoglobin and is a novel approach for increasing oxygen availability in the wound bed in diabetic foot ulcer patients. Its mode of action is to bind oxygen from the atmosphere and diffuse it into the wound bed to accelerate wound healing in slow-healing wounds. Patients and methods: Wound healing outcomes, that is, wound size, pain, percentage of slough, and exudate levels, were compared retrospectively to a similar cohort of patients treated over the same period the previous year. The same inclusion and exclusion criteria applied to both groups. Results: All 20 (100%) hemoglobin spray-treated patients and 15 (75%) control patients experienced some wound healing by week 4, with 5 (25%) and 1 (5%), respectively, achieving complete wound closure. At week 4, mean wound size reduction was 63% in the hemoglobin spray group versus 26% for controls, increasing to 95% reduction at week 28 in the hemoglobin spray group versus 63% for controls ( p< 0.05 at all timepoints). Hemoglobin spray was associated with substantially lower pain scores using a 10-cm visual analogue scale, with 19/19 patients (100%) being pain-free from week 12 onwards, compared to 6/18 patients (33%) in the control group. At week 28, 2/18 patients (11%) in the control group still had pain. Both groups had similar baseline slough levels, but hemoglobin spray-treated wounds had slough completely eliminated after 4 weeks versus 10% mean reduction in the control group ( p< 0.001). Hemoglobin spray was associated with markedly reduced exudate levels; within 4 weeks, no patients had high exudate levels in the hemoglobin spray group versus 5 in the control group. Conclusion: Standard wound care plus hemoglobin spray results in improvements in wound closure, wound size reduction, pain, slough, and exudate levels compared to control patients for chronic diabetic foot ulcer treatment.